BASIC PRINCIPLES OF UTILITARISM IN PHILOSOPHY (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article discusses the main principles of utilitarianism in philosophy. Utilitarianism is a philosophical perspective that evaluates the ethical value of human actions based on their effectiveness and the aim of maximizing human happiness. The article analyzes the core concepts of utilitarianism, including the principles of “happiness maximization” and “assistance,” as well as the historical development of utilitarianism and its key representatives, such as Jeremy Bentham and John Stuart Mill. It also examines the practical application of utilitarianism, its impact on social and ethical issues, as well as criticisms and alternative viewpoints. Examples are provided of how the principles of utilitarianism are applied in contemporary ethical discussions and politics. The article helps to gain a deeper understanding of the philosophical foundations of utilitarianism and its significance in social life. The philosophy of utilitarianism plays an important role in decision-making within society. It proposes principles aimed at maximizing individual and collective welfare. However, its application raises ethical debates, as issues of personal rights and justice are sometimes overlooked. The position of utilitarianism in society is defined through its principles, practical application, and ethical constraints.
Keywords: Values, morality, freedom, justice, technology, utilitarianism, philosophy, ethics.